"Numerical modelling of PM10 dispersion in open-pit mines",. (November 2020) - Sumanth, Chinthala; Khare, Mukesh; Shukla, Komal
Graphical abstract: Image 1 Highlights: Provides a mathematical tool to estimate in-pit retention by including gravity. The model predicts favourable meteorological conditions for mining activities. PM10 concentrations at various depths within the mine are estimated. The effect of external wind on the dispersion of PM10 has been estimated.